PREDIKSI KEMAMPUAN PERUSAHAAN PADA MASA KRISIS: PERBANDINGAN JUDGMENT DENGAN STATISTIK - INDRA WIJAYA KUSUMA; YAVIDA NURIM (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
This study examines the accuracy of capability of companies to survive during the Indonesia monetary crisis in 1997-1999. Several studies have developed models to predict the bankcrupty of firms and found that some financial ratios are useful in predicting the possibility of bankcrupty. This study uses those ratios that have been proved useful in predicting bankcruptcy to predict the survival of Indonesian companies during the crisis. in addition, this study also uses human prediction. Research on comparing human prediction and statistics methods in the auditing areas have found that human is superior in prediction because human possesses human information processing which consider other data (besides financial data) in prediction. The results show taht human prediction is inferior in predicting companies' capability to survive the crisis and work experience affects the accuracy of the human judgment prediction. However, the study also shows that some ratios that are preferably used by human in predicting are consistent with the ratios used in previous studies. The potential bias in this study may be causes by the subjects (human) who participated in the field experiment. Future study is needed to use subjects who are financial or credit analysts in order to have better human prediction results.